Behavioral Comfort and Nutritional Problems of the Hungarian Soldiers in World War II - Zoltan, Magyar; Tamas, Revai (Pakistan Journal of Nutrition, 2011)
Exercising in the cold weather brings some unique challenges for soldiers who participate in cold environment. Anyone who exercises in cold weather needs to take a few precautions in order to stay comfortable, safe and still perform at an optimal level when temperatures drop. Suitable clothing and proper nutrition helps regulate the core temperature, keeps the body warm and provides enough fuel for the working muscles. This paper describes the behavioral comfort and nutritional problems of the Hungarian soldiers in WWII and shows our results with thermal manikin.